Determinant Factor of Firm Value in Covid-19 Pandemic: Role of Dividend Policy as Mediating Variable - Gregorius Paulus Tahu; Anik Yuesti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
COVID-19 has affected financial markets around the world. The purpose of this study is to analyze Determinant Factor of Firm Value in Covid-19 Pandemic: Role of Dividend Policy as Mediating Variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The research sample was taken by using purposive sampling method with a sample of 16 manufacturing companies. This study uses multiple linear regression and Sobel's test as data analysis tools to measure dividend policy as a mediating variable between profitability, liquidity, free cash flow, leverage, firm growth, investment opportunities on firm value in covid-19 pandemic. The results of the study shown that profitability, liquidity, free cash flow, leverage, firm growth, and Covid-19 influence the dividend policy and firm value. But investment opportunities is not influence the dividend policy and firm value.  While based on the results Sobel test with interactions, this study found that dividend policy mediated the effect of profitability, liquidity, free cash flow, leverage, firm growth, Covid-19 on the firm value. The study extends empirical evidence on factor determinants of firm value in Covid-19 pandemic which are currently reported to be inconclusive. In addition, the study fills the gaps in the existing literature by focusing on the issue of firm value determinants in the context of dividend policy as mediator variable in Covid-19 pandemic.